What makes a good citizen online?: the emergence of discursive citizenship norms in social media environments - Gagrčin, Emilija; Porten-Cheé, Pablo; Leißner, Laura; Emmer, Martin; Jørring, Louise (Social media + society, 2022)
The importance of citizenship norms—shared understandings of how citizens ought to participate in society—has been discussed at length in the past two decades, particularly in conversations around changing notions of citizenship in the digital age. Yet, most studies have gravitated between the two poles of dutiful and self-actualizing citizenship. In this study, we explore which citizenship norms people express related to their political participation in social media environments and which affordances and experiences in social media environments shape these norms. Through interviews and focus group discussions, we found that citizenship norms emerge in response to positive and negative experiences in social media environments. We found three groups of norms that are distinctive to the networked environments of social media: individual information care, discourse care, and considered contribution. These can serve as conceptual frames for understanding the normative underpinnings of discursive participation in social media environments from the perspective of ordinary citizens.
Gesehen am 04.06.2022